The Coaching of Family Welfare and Empowerment Group of Krueng Barona Jaya through the Making of Soap - Mirna Rahmah Lubis; Husni Husin; Lia Mairiza; Yoessi Oktarini (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The Krueng Barona Jaya is a sub-district in Aceh Besar District, Aceh Province, Indonesia. This sub-district is located near the Ulee Kareng area, Banda Aceh. The Krueng Barona Jaya sub-district has at least more than 16,000 people spread across a number of locations. Most of the residents in Krueng Barona sub-district earn their living as farmers, domestic workers, civil servants, entrepreneurs, and 31.53% have temporary jobs. This situation can be improved by providing various training to residents to help them establish their own or group businesses. The community service activity is intended to improve public understanding about technology of making liquid soap. To achieve this objective the team sincerely helped provided training on the process of making liquid soap for mothers in the family-welfare-empowerment group. The results of interviews with the community and sub-district officials showed that the women of the group were very enthusiastic in participating in soap making training and other similar activities. The results of interviews with the community and sub-district officials showed that the women of the group were very enthusiastic in participating in soap making training and other similar activities. The results of the discussion indicated that the participants’ mastery of making soap was very good. This training and coaching opens people’s mind to change their habits and thinking patterns.